Attitude of Medical School Students in China Towards Genetic Testing and Counseling Issues in FXS. Issue 6 (18th August 2013) - Li, Jia; Huang, Wen; Luo, Shiyu; Lin, Yunting; Duan, Ranhui
Abstract: Fragile X syndrome (FXS) is the most common form of inherited intellectual disability. However, genetic testing protocols and genetic counseling guidelines for FXS are not yet established in mainland China. In the present study, we conducted a comprehensive analysis using a self‐administered questionnaire among students at the Xiangya medical school to investigate their attitude towards genetic testing and counseling issues of FXS. We have gained a general understanding of the attitudes of medical students towards these FXS issues in China. This information is of immense importance to develop appropriate genetic tests and to train counselors for FXS. As the medical school students surveyed are prospective physicians who will be a part of the Chinese health system, our survey was focused on the basic knowledge of FXS, population‐based FXS screening, confidentiality and reproductive options for mutation carriers. The study demonstrated that only less than one third of the participants had heard about FXS. 94.6 % of participants were in favor of FXS screening for women in their reproductive age who had a genetic history of FXS. Furthermore, only half of the participants would inform their families about their genetic status in case of positive test results, and more than half of the participants supported natural conception and prenatal diagnosis for FXS mutation carriers. Additional findings and research implications are also discussed. This survey targeting potential doctors provides important information for the development of FXS genetic test and counselor training for the Chinese health system.